Fun for the secret seven - Blyton, Enid (Hodder Children's, London., 2002)
An enduringly popular series, now with fun new covers! The Seven are desperate to help Tolly and his sick horse, Brownie. But where can they hide an old man and his horse? And can they protect Brownie from thieves?
Keywords: English , Fiction